Other Voices : a Study of the Late Poetry of Luis Cernuda - Coleman, Alexander (Project Muse, 2018)
Coleman begins his book with the following supposition: that Luis Cernuda was a poet whose primary impulse in his art was the suppression of the subjective and the consequent objectivization of poetry.
Prepared as a doctoral dissertation, Columbia University, 1964.
Keywords: Cernuda, Luis.; Cernuda, Luis; Electronic books.